Teak-Soil Interaction: Teak (Tectona grandis) Plantations Impact and are Impacted by Soil Properties and Fertility in Southwestern Ghana - Michael Asigbaase; Michael Annan; Daniel Adusu; Simon Abugre; Collins Ayine Nsor; Samuel Kumi; Selina Adutwumwaa Acheamfour (Applied and Environmental Soil Science)
Teak (Tectona grandis) is one of the most widely established plantation species globally due to its potential for degraded forest restoration, timber supplementation, and easing pressure on natural forest resources. However, the extent to which plant-soil interactions in teak plantations impact tree growth and productivity and soil nutrient dynamics is not well understood. This study assessed the impact of teak plantations on soil physicochemical properties as well as the influence of soil properties and fertility on teak growth. The study was conducted in teak plantations aged 5, 10, 15, 20, and over 20 years and an adjacent natural forest remnant. We established three 25 m × 25 m plots in each teak plantation and recorded the diameter at breast height (DBH), height, crown length, and depth of all trees. We collected 54 soil samples at 0–20 cm depth and analysed them for 29 soil parameters. The study revealed that teak plantations resulted in a decline in soil N (45%–81%) and available P (63%–98%) concentration, while soil pH improved by 0.41–0.64 units. However, soil organic carbon, K, Mg, Ca, and Na concentrations and their ratios were unaffected with teak plantations over time. Also, soil textural characteristics, acidity, and nutrient ratios were observed to influence tree-related characteristics such as DBH and crown dimensions (crown, diameter, breadth, length, and volume). Three principal components (PC1, PC2, and PC3) explained 69% of the overall variability and were significantly related to tree crown parameters, height, and diameter at breast height. We concluded that site selection and tailored integrated soil fertility management for each plantation age are critical to sustainable teak production as teak plantations both affect and are affected by soil properties. The study recommends the adoption of management practices aimed at maintaining soil nutrient balance to ensure the long-term growth and ecological sustainability of teak plantations.